Determination of the Anticancer Drug Sorafenib in Serum by Adsorptive Stripping Differential Pulse Voltammetry Using a Chitosan/Multiwall Carbon Nanotube Modified Glassy Carbon Electrode. Issue 2 (29th July 2015) - Karadas‐Bakirhan, Nurgul; Patris, Stéphanie; Ozkan, Sibel A.; Can, Alp; Kauffmann, Jean‐Michel
Abstract: Adsorptive stripping differential pulse voltammetry (AdSDPV) was applied to the assay of sorafenib in human serum sample. Cyclic voltammetry at a carbon based screen printed electrode (SPE) permitted to detect the irreversible oxidation of SOR with formation of a new compound reversibly oxidized at a lower potential. Quantitative assays were realized using a chitosan/carboxylic acid functionalized multiwalled carbon nanotube modified glassy carbon electrode in 0.1 M phosphate buffer pH 7.0 in the presence of 50 % methanol. The AdSDPV method provided two linear responses within the concentration ranges 1×10 −8 –8×10 −8 M and 1×10 −7 –8×10 −7 M in serum with LOQ and LOD of 3.2×10 −9 and 9.6×10 −10 of lower linear range, respectively. The recovery of sorafenib in spiked serum was 97.5 %. Abstract :